The Practitioner's Bookshelf: New Books on Undocumented Storytellers in the United States and on the Crime of Aggression in International Law. (5th December 2019) - Valente, Rubia R; Phillips, Brian
Abstract: In this instalment of 'The Practitioner's Bookshelf'—a new feature of the JHRP Review section containing brief reviews of recent publications of particular interest to human rights practitioners—Rubia R. Valente (Baruch College, City University of New York) discusses an analysis of narratives from the immigrant rights movement in the USA and Brian Phillips (Reviews Editor, JHRP) assesses a study of the crime of aggression in international law.